Clinical pharmacist roles in primary care networks - Petty, Duncan (Prescriber (London, England), 2019)
Clinical pharmacists are important members of the multidisciplinary team within primary care networks (PCNs), which were established across England in July 2019. This article discusses the roles that will be expected of clinical pharmacists within PCNs and how these roles are likely to develop in the future.